Labor Market Issues in China. - Giulietti, Corrado; Tatsiramos, Konstantinos; Zimmermann, Klaus F. (Emerald Group Publishing Limited, 2013)
After three decades of economic reform, China is experiencing substantial demographic changes and a steady structural transformation toward a market economy. This volume presents fresh knowledge on labor market issues in China including topics such as: occupational choice and mobility, over-qualification and hiring, cost of displacement, and the performance of urban and rural social insurance programs.
Notesreferences.
Keywords: Labor market -- China.; China.; elektronické knihy; electronic books